2014
DOI: 10.1159/000358841
|View full text |Cite
|
Sign up to set email alerts
|

Review of Psychodynamic Psychotherapy Neuroimaging Studies

Abstract: The clinical efficacy of psychodynamic psychotherapy (PDT) has undergone extensive study and review. Recently, researchers have studied the effects of this treatment on brain metabolic or synaptic activity, but the collective findings have never been reviewed. The objective of this review was to describe the findings of all neuroimaging studies of any form of PDT treatment. An extensive literature search through databases along with surveying of research groups were undertaken to acquire all available publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 31 publications
0
12
0
3
Order By: Relevance
“…Although understudied relative to other interventions [5], psychodynamically oriented therapies have been preliminarily associated with synaptic and metabolic changes in limbic, midbrain, and prefrontal regions [6]. However, heterogeneity of treatment (even within-study) and lack of discrimination between responders and nonresponders limit previous studies in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Although understudied relative to other interventions [5], psychodynamically oriented therapies have been preliminarily associated with synaptic and metabolic changes in limbic, midbrain, and prefrontal regions [6]. However, heterogeneity of treatment (even within-study) and lack of discrimination between responders and nonresponders limit previous studies in the field.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact mechanisms through which psychotherapy acts are not well understood. An influential model of the mechanism of action of psychotherapy draws on data from the considerable number of studies that have applied clinical neuroscience approaches (primarily functional neuroimaging) to identify the brain-behavior circuits that change during therapy (for reviews, see Abbass, Nowoweiski, Bernier, Tarzwell, & Beutel, 2014;Beauregard, 2007; DeRubeis, Siegle, & Hollon, 2008;Disner, Beevers, Haigh, & Beck, 2011;Frewen, Dozois, & Lanius, 2008;Messina, Sambin, Palmieri, & Viviani, 2013). According to this model, psychotherapy may act by promoting the effectiveness of control processes of executive nature, whose neurobiological substrate may be located in prefrontal areas (see Fig.…”
mentioning
confidence: 99%
“…In their meta-analysis, Diener, Hilsenroth, and Weinberger (2007) concluded that facilitation of affective experience and expression by the therapist contributed consistently to positive treatment outcomes with a magnitude of r = 0.30 which was comparable to the effect of the therapeutic alliance. Indeed, a recent review of neuroimaging studies demonstrated that therapeutic improvement in PP was associated with changes in neuronal networks subserving emotional processes (Abbass, Nowoweiski, Bernier, Tarzwell, & Beutel, 2014). However, patients' emotional experiencing has received relatively little empirical attention in psychodynamic therapy research (Fisher et al, 2016), along with specific therapeutic actions focusing on affect (Subic-Wrana et al, 2016;Whelton, 2004).…”
Section: The Need For a New Manualmentioning
confidence: 99%